IMPLEMENTASI PROGRAM OPTIMALISASI CARA UNTUK MANDIRI PANGAN (OCU MAPAN) DI KELURAHAN LANGGINI KECAMATAN BANGKINANG KOTA - Mhd. Wahyu Ramadhan; Sujianto Sujianto (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Kampar Regency is one of the regions in Indonesia that has a large potential for food production. Langgini Village located in Kampar Regency has the potential of an unused yard. in food independence and the lack of community food needs. The purpose of this study was to determine the implementation of how to optimize the food independent program in Kampar district and the inhibiting factors for optimizing the program for food independence in Kampar district. This research method uses a qualitative method with a descriptive pen, as well as collecting data obtained through observation, interviews and documentation, then analyzed based on the problems found in the study. The findings of this study indicate that the program for optimizing ways to be self-sufficient in food is currently running well, but there are inhibiting factors, namely human resources (HR), limited funds and the COVID-19 pandemic.